The Reflection of Japanese Culture in Snow Country by Yasunari Kawabata - Meria Zakiyah Alfisuma; Eka Susylowati; M. Masqotul Imam Romadlani; Achmad Fanani (Unipdu Jombang, 2023)
Yasunari Kawabata is a Japanese writer who won the Nobel Prize in literature. One of his most popular novels entitled Snow Country is full of Japanese cultural values. The purpose of this study is to examine the extent to which the novel Snow Country reflects the life and culture of Japanese society. The method used is descriptive qualitative which describes and analyzes the collected data taken from the quotations of the novel. In analyzing the data, the writers use the mimetic approach and the concept of culture by Hammersley (2019) to reflect aspects of Japanese culture in literary works based on reality. The result of the study proves that the cultural depiction in Snow Country is in accordance with the cultural reality that exists in Japan, and based on the concept of culture by Hammersley, the culture found in this novel are divided in the form of Japanese cultural tools, cultural environment and the life of Geisha. The Japanese cultural tools including traditional drink ‘Sake’, traditional clothes/dress ‘Kotatsu, Kimono and Yukata’, art ‘Kabuki’ and music ‘Shamisen’, art or mode of Japanese houses in Daimyo Period, Traditional Japanese Houses ‘Shouji Sliding Doors’ and ‘Tatami’. Japanese cultural environments are found by the depiction of situations in Hot Springs ‘Onsen’, habits of Japanese society in autumn and winter. The last, one of the cultures of Japanese is also depicted by the art of Geisha, that is the life of Geisha and Geisha house “Okiya”, Keywords: mimetic, novel, culture, and Japan